2022
DOI: 10.1111/1541-4337.13025
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multi‐omics approaches to understand microbiome assembly in Jiuqu, a mixed‐culture starter

Abstract: The use of Jiuqu as a saccharifying and fermenting starter in the production of fermented foods is a very old biotechnological process that can be traced back to ancient times. Jiuqu harbors a hub of microbial communities, in which prokaryotes and eukaryotes cohabit, interact, and communicate. However, the spontaneous fermentation based on empirical processing hardly guarantees the stable assembly of the microbiome and a standardized quality of Jiuqu. This review describes the state of the art, limitations, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 194 publications
0
11
0
Order By: Relevance
“…Daqu is one of the Chinese Baijiu Jiuqus (starters). The main ingredient is raw wheat, supplemented by a percentage of barley and peas (Kang et al, 2022). The raw materials are moistened, grinder, and shaped into blocks and then sent to the incubation room to be naturally inoculated with environmental microorganisms for fermentation, and the finished product is named Daqu because of its shape (Zheng et al, 2011).…”
Section: Definition and Classification Of Baijiu Daqumentioning
confidence: 99%
See 2 more Smart Citations
“…Daqu is one of the Chinese Baijiu Jiuqus (starters). The main ingredient is raw wheat, supplemented by a percentage of barley and peas (Kang et al, 2022). The raw materials are moistened, grinder, and shaped into blocks and then sent to the incubation room to be naturally inoculated with environmental microorganisms for fermentation, and the finished product is named Daqu because of its shape (Zheng et al, 2011).…”
Section: Definition and Classification Of Baijiu Daqumentioning
confidence: 99%
“…In the Daqu type division, mainly in Daqu fermentation maximum temperature (High-temperature Daqu, Middle-temperature Daqu, Low-temperature Daqu), flavor characteristics (Maotai-flavor Baijiu Daqu, Luzhou-flavor Baijiu Daqu, Fen-flavor Baijiu Daqu, etc. ), shape (Bag Daqu, Brick Daqu), production methods (Mechanical Daqu, Handmade Daqu), functional characteristics (Traditional Daqu, Fortified Daqu) to divide (Zheng et al, 2018;Zuo et al, 2020;Kang et al, 2022;Figure 1A).…”
Section: Definition and Classification Of Baijiu Daqumentioning
confidence: 99%
See 1 more Smart Citation
“…We placed the terroir element at the base of the yellow pyramid, reflecting its support for the other elements. Terroir determines the phenotype of raw materials, influences the control of craft parameters, and plays a role in the assembly of SFFM (Conacher et al., 2021; Gilbert et al., 2014; Kang et al., 2022; Kelly et al., 2012; Tan et al., 2022). Although terroir is the basis of the fermentation system, its direct contribution to products is usually thought of as a geographical indication endowing products with regional cultural features and global recognition (Lucini et al., 2020).…”
Section: Microbial Community Assembly Of Sffmmentioning
confidence: 99%
“…Some research has shown that bioreactors with high surface‐area‐to‐volume ratios give a higher product yield than traditional cultures or handmade substrates (Kang et al., 2022; Qian et al., 2019). To incorporate this, functional guilds and initial microbiota could be printed in hydrogels using living‐cell printing technology (He et al., 2022) to better realize species and community coalescence.…”
Section: Integrated Design Strategy and Perspectivesmentioning
confidence: 99%